TINJAUAN AZ ZARNUJI TERKAIT RELEVANSI KEWAJIBAN DAN HAK SISWA DALAM KONTEKS PENDIDIKAN MODERN - Yugo, Tri Yugo (UIN Antasari Banjarmasin, 2024)
This study aims to examine Imam Az-Zarnuji's views on the obligations and rights of students in the context of the book